Effect of Cu, Cr and Ni alloying elements on mechanical properties and atmospheric corrosion resistance of weathering steels in marine atmospheres of different aggressivities. Issue 1 (18th August 2017) - Cano, H.; Díaz, I.; de la Fuente, D.; Chico, B.; Morcillo, M.
Abstract : This paper studies the individual and combined effect of adding Cu (0.26–1.06 wt%), Cr (0.54 wt%) and Ni (0.92–2.92 wt%) alloying elements to carbon steel with regard to mechanical behaviour and atmospheric corrosion resistance in two marine atmospheres with different chloride deposition rates (20 and 71 mg Cl − /m 2 · d). Mechanical properties are assessed in terms of yield strength, ultimate strength, elongation, hardness and weldability, while atmospheric corrosion resistance is evaluated by determination of corrosion losses, rust layer structure, and nature of the corrosion products formed. The best atmospheric corrosion resistance is obtained with weathering steel (3 wt% Ni), which would be suitable for use unpainted in marine atmospheres of moderate salinity (≤20 mg Cl − /m 2 · d), though a longer cooling time would be required during its manufacture in order to assure adequate weldability. Abstract : The principal limitation of conventional weathering steels (WS) is that they need to be protected during marine atmospheric exposure. In the research the effect promoted by adding Cu, Cr and Ni has been determined. The best corrosion resistance in low aggressive marine atmospheric is obtained when Ni (3 wt%) is added.